Analysis of The Influence of Return on Equity on Sharia Stock Price Moderated by Corporate Social Responsibility - Zikra Agusti Humaira (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This research aims to determine the effect of Return On Equity (ROE) on Sharia Share Prices of the Property Sector Moderated by Corporate Social Responsibility (CSR). The population of this research is all property sector companies listed on the Indonesia Stock Exchange from 2011 to 2017. The research sample was taken using a purposive sampling method, so that a sample of 12 companies was obtained. The data analysis technique used is the panel data regression method which is a combination of cross section data and time series data using Eviews 7 software. The results of the analysis show Return On Equity (ROE) does not have a significant effect on the price of sharia shares in the property sector and Corporate Social Responsibility (CSR) is proven to strengthen the effect of ROE on the sharia stock price of the property sector. The findings of this study will be useful for relevant policy makers because disclosure of CSR in financial statements will provide positive sentiment that will increase investor confidence to invest.Penelitin ini bertujuan untuk mengetahui pengaruh Return On Equity (ROE) Terhadap Harga Saham Syariah Sektor Properti Yang Dimoderasi Oleh Corporate Social Responsibility (CSR). Populasi penelitian ini adalah seluruh perusahaan sektor properti yang terdaftar di Bursa Efek Indonesia tahun 2011 hingga 2017. Sampel penelitian diambil menggunakan metode purposive sampling, sehingga diperoleh sampel sebanyak 12 perusahaan. Teknik analisis data yang digunakan adalah metode regresi data panel yang merupakan gabungan dari data cross section dan data time series dengan menggunakan software Eviews 7. Hasil analisis menunjukkan Return On Equity (ROE) tidak memiliki pengaruh yang signifikan terhadap harga saham syariah sektor properti dan Corporate Social Responsibility (CSR) terbukti memperkuat pengaruh ROE terhadap harga saham syariah sektor properti. Temuan penelitian ini akan bermanfaat bagi pengambil kebijakan terkait karena pengungkapkan CSR dalam laporan keuangan akan menjadi nilai yang akan menambah kepercayaan investor untuk melakukan investasi.Kata Kunci : Harga Saham Sektor Properti, ROE, CSR